Study of traffic delay at signalised junction - Boddu, Shruti Shree. (2013)
Traffic delay is the additional traffic time experienced by a vehicle due to various circumstances that impede the desirable movement of vehicles. It is measured as the difference between the actual travel time and the free-flow travel time. Traffic delay can occur at signalised junctions due to the signal timings. Hence, to minimise traffic delay, signal timings can be adjusted according to the specific needs of a junction. However, the first step to this is to accurately calculate the traffic delay at that junction.